FunCoup 5: Functional Association Networks in All Domains of Life, Supporting Directed Links and Tissue-Specificity. Issue 11 (28th May 2021) - Persson, Emma; Castresana-Aguirre, Miguel; Buzzao, Davide; Guala, Dimitri; Sonnhammer, Erik L.L.
Graphical abstract: Highlights: Comprehensive functional association networks from 11 evidence types for 22 species. Evidences, gold standards and genomes have been updated to the latest sources. Includes a host-virus network for the SARS-CoV-2 virus and human proteins. Features directed links inferred from ChIP-seq data and tissue-specific subnetworks. Abstract: FunCoup (https://funcoup.sbc.su.se ) is one of the most comprehensive functional association networks of genes/proteins available. Functional associations are inferred by integrating different types of evidence using a redundancy-weighted naïve Bayesian approach, combined with orthology transfer. FunCoup's high coverage comes from using eleven different types of evidence, and extensive transfer of information between species. Since the latest update of the database, the availability of source data has improved drastically, and user expectations on a tool for functional associations have grown. To meet these requirements, we have made a new release of FunCoup with updated source data and improved functionality. FunCoup 5 now includes 22 species from all domains of life, and the source data for evidences, gold standards, and genomes have been updated to the latest available versions. In this new release, directed regulatory links inferred from transcription factor binding can be visualized in the network viewer for the human interactome. Another new feature is the possibility to filter by genes expressed in a certain tissue in the network viewer. FunCoup 5 further includes the SARS-CoV-2 proteome, allowing users to visualize and analyze interactions between SARS-CoV-2 and human proteins in order to better understand COVID-19. This new release of FunCoup constitutes a major advance for the users, with updated sources, new species and improved functionality for analysis of the networks.